TiO2 Nanoparticles Green Synthesis Utilising Cynara scolymus for Efficient removal of Pb (II) ions - Fatma Abbas Khazaal (Journal of Wasit for Science and Medicine, 2026)
Titanium dioxide nanoparticles were synthesized using Cynara scolymus seed extract as a reducing and stabilizing agent. TiO2 NPs were fully characterized by FT-IR, SEM, and TEM techniques to confirm the formation of stable nanoparticles with a spherical morphology and sizes ranging from 10 to 30 nm. TiO2 NPs demonstrated considerable and instantaneous efficacy to precipitate lead ions (Pb²⁺) from aqueous solutions without pH or contact time adjustments. The green synthesis approach offers a sustainable and cost-effective alternative to traditional methods. Also, suggesting a potential application of synthesized nanoparticles for environmental remediation.
Keywords: Titanium dioxide nanoparticles; green synthesis; lead removal; ultrasound-assisted extraction